Dissection of the Ovulatory Process Using ex vivo Approaches - Tokmakov, Alexander A.; Stefanov, Vasily E.; Sato, Ken-Ichi (Frontiers in Cell and Developmental Biology, 2020)
Ovulation is a unique physiological phenomenon that is essential for sexual reproduction. It refers to the entire process of ovarian follicle responses to hormonal stimulation resulting in the release of mature fertilization-competent oocytes from the follicles and ovaries. Remarkably, ovulation in different species can be reproduced out-of-body with high fidelity. Moreover, most of the molecular mechanisms and signaling pathways engaged in this process have been delineated using in vitro ovulation models. Here, we provide an overview of the major molecular and cytological events of ovulation observed in frogs, primarily in the African clawed frog Xenopus laevis, using mainly ex vivo approaches, with the focus on meiotic oocyte maturation and follicle rupture. For the purpose of comparison and generalization, we also refer extensively to ovulation in other biological species, most notoriously, in mammals.